Step [videorecording (DVD)] - Dofat, Paula; Giraldo, Blessin; Grainger, Cori (Twentieth Century Fox Home Entertainment, 2017)
The senior year of a girls' high school step dance team against the background of inner city Baltimore. Empowered by their teachers, coaches, families, and each other, they strive to win a championship and go to college.